Learning internal iliac artery ligation and pelvic ureter course through cadaveric dissections - Mahale, Arun R.; Gosavi, Anjali G.; Ugale, Mahesh S.; Diwan, Chaya V.; Sukre, Shivaji B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Few surgical procedures, although vital, are not learnt and mastered during postgraduate courses in Obstetrics and Gynecology. Internal iliac artery ligation and tracing course of ureter are few of such surgical procedures. Cadaveric dissection sessions organized during postgraduate courses and as CME sessions (continued medical education) have proved useful in learning such unlearnt procedures. This article shares experiences from teaching internal iliac artery ligation, pelvic ureter course tracing and principles of many other unusual gynaecological surgical procedures to Obstetrics and Gynecology specialists and postgraduate students through CME programs involving cadaveric dissection. Methods: This involved organizing and conducting four cadaveric dissection CME workshops at three different teaching institutions. The components of these CMEs were lectures with power point presentations and two-way audio-visual interactive sessions while pelvic anatomy was demonstrated on cadavers through live dissections. Each CME was concluded by tactile experience to each delegate by handling the dissected cadavers; this was made possible by limiting delegate registration to 50 at each CME. Results: The surgical skills of internal iliac artery ligation and tracing course of pelvic ureter, which are not adequately and confidently learnt in routine postgraduate tenure, could be effectively transferred through cadaveric dissection. Conclusions: Revisiting anatomy dissection halls helps in learning rare but lifesaving surgical techniques. This can be achieved by arranging cadaveric dissection CMEs for practicing specialists. Such CMEs should be organized regularly and should be integrated into postgraduate curriculum.